Implementasi Integrasi Disk Operating Sistem (DOS) dengan Sistem Embedded Logger Cuaca Berbasis Automatic Voltage Regulator (AVR) - Ratu Fitri Salsabila; Dirmansyah Dirmansyah; Pratama Heru (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
The development of embedded sistem technology is now widely used to support automatic environmental data recording processes, such as temperature, humidity, and air pressure. However, most existing weather data loggers still operate independently and are not directly connected to a computer. As a result, data collection and processing must be done manually, which is less efficient and prone to data loss. The main problem in this research is the lack of integration between microcontroller-based data loggers and simple computer operating sistems such as the Disk Operating Sistem (DOS), making it difficult to automatically store and access recorded data. This study aims to develop an embedded weather data logger sistem based on the AVR microcontroller integrated with DOS. The development process uses the waterfall model, consisting of sistem planning, requirement analysis, sistem design, coding, testing, and implementation. The designed sistem records weather parameters in real time and stores them in a file format that can be directly read by DOS without requiring additional conversion processes. The test results show that the sistem runs stably, records data accurately, and can be easily accessed through a computer. Integration with DOS allows data storage and retrieval processes to be faster and more efficient. Therefore, this sistem provides a practical solution for automatic weather monitoring that is reliable, time-saving, and easy to use in various environmental conditions.